(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2026)
Effective Quality Risk Management (QRM) is vital for informed decision-making and regulatory assurance; however, deficient systems often lead to suboptimal pharmaceutical products. This study assessed QRM implementation and effectiveness within Ethiopian Pharmaceutical Manufacturers (EPMs). A cross-sectional descriptive study was conducted among key personnel at six EPMs in Addis Ababa. Data were collected via self-administered questionnaires and analyzed using descriptive and inferential statistics in SPSS version 28. Findings revealed that while most EPMs have established risk frameworks, significant deficiencies persist in formal risk identification and quantitative assessment of likelihood and impact. A critical gap in regular staff training was also observed. Primary operational risks included raw material shortages, equipment malfunctions, and exchange rate fluctuations. Although foundational proficiency in identification and monitoring was noted, inconsistent formal application and underutilization of post-marketing systems, such as pharmacovigilance, remain problematic. To enhance compliance and safety, manufacturers should prioritize supply chain diversification, technological investment, and mandatory, ongoing QRM training programs.